The role of sheet-like TiO2 in polyamide reverse osmosis membrane for enhanced removal of endocrine disrupting chemicals - Nor Akalili, Ahmad; Goh, Pei Sean; Nur Alyaa Syfina, Zakaria; Rosmawati, Naim; Mohd Sohaimi, Abdullah; Ahmad Fauzi, Ismail; Norbaya, Hashim; Nirmala Devi, Kerisnan@Kerishnan; Nasehir Khan, E.M. Yahaya; Alias, Mohamed (Elsevier, 2024)
Thin film composite (TFC) reverse osmosis (RO) membrane shows good promise for treating wastewater containing endocrine disrupting chemical (EDC) pollutants. The incorporation of functional materials with exceptional structural and physico-chemical properties offers opportunities for the membranes preparation with enhanced permselectivity and better antifouling properties. The present study aims to improve the EDC removal efficiency of TFC RO membrane using two-dimensional titania nanosheets (TNS). RO membrane was prepared by incorporating TNS in the dense layer of polyamide (PA) layer to form thin film nanocomposite (TFN) membrane. The TNS loading was varied and the influences on membrane morphology, surface hydrophilicity, surface charge, as well as water permeability and rejection of EDC were investigated. The results revealed that the inclusion of TNS in the membrane resulted in the increase of water permeability and EDC rejection. When treating the mixture of bisphenol A (BPA) and caffeine at 100 ppm feed concentration, the TFN membrane incorporated with 0.05% TNS achieved water permeability of 1.45 L/m2·h·bar, which was 38.6% higher than that of unmodified TFC membrane, while maintaining satisfactory rejection of >97%. The enhancement of water permeability for TFN membrane can be attributed to their hydrophilic surface and unique nanochannel structure created by the nanoscale interlayer spacing via staking of TiO2 nanosheets. Furthermore, the 0.05TFN membrane exhibited excellent fouling resistance towards BPA and caffeine pollutants with almost 100% flux recovery for three cycles of operations.